Food safety culture : creating a behavior-based food safety management system - Yiannas, Frank (Food microbiology and food safety series, 2009)
Food safety awareness is at an all time high, new and emerging threats to the food supply are being recognized, and consumers are eating more and more meals prepared outside of the home. Achieving food safety success in this changing environment requires going beyond traditional training, testing, and inspectional approaches to managing risks